Analisis Kinerja Keuangan Klub Sepak Bola Bali United FC - Kumalasari, Rizky; Yudi; Olimsar, Fredy (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
This research aims to determine the financial performance of the Bali United FC football club. This research uses quantitative descriptive analysis techniques using 10 general and specific financial ratio indicators. The data used is secondary data in the form of financial reports from 2018 to 2022 which come from the company’s official website. The results of this research show that the financial performance of the Bali United FC football club generally has a good level of liquidity and solvency, but the level of profitability is still not good. The results of calculations using special ratios show that Bali United FC is able to manage assets and operating expenses well, as well as generating quite good sales and operating cash flow